First measurement of the cross section for top-quark pair production in proton-proton collisions at root s=7 TeV - Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; Hammer, J; et al. (2011)
The first measurement of the cross section for top-quark pair production in pp collisions at the Large Hadron Collider at center-of-mass energy s=7 TeV has been performed using a data sample corresponding to an integrated luminosity of 3.1±0.3 pb-1 recorded by the CMS detector. This result utilizes the final state with two isolated, highly energetic charged leptons, large missing transverse energy, and two or more jets. Backgrounds from Drell-Yan and non-W/Z boson production are estimated from data. Eleven events are observed in the data with 2.1±1.0 events expected from background. The measured cross section is 194±72(stat.)±24(syst.)±21(lumi.) pb, consistent with next-to-leading order predictions. © 2010 CERN.